Praktik Metode Penginjilan Pada Mata Kuliah Metode Penginjilan STT Simpson Ungaran - Jamin Tanhidy (Sekolah Tinggi Teologi Simpson, 2017)
Jamin Tanhidy, A Practise of Evangelis Method in Evangelis Method lecture of STT Simpson Students. Evangelism is the Great Commission of our Lord Jesus Christ (Mat. 28:18-20), so that STT Simpson emphasize on the fulfillment of the Great Commission. This study describes the achieve-ments of the implementation of Evangelism practices and what are the factors inhibiting the adoption of Evangelis practices method on students participating in courses Evangelis method even academic year 2014-2015. This method of research used in this research is qualitative research. The data in this study were obtained through focus group discussions, interviews open, and report student practice. The results obtained is 1) The achievement of student practice only reached the stage of submission of the Gospel, 2) Factors difficulty implementing Evangelis practices are internal factors: 55.55%, and external factors: 44.44%. Jamin Tanhidy, Praktik Metode Penginjilan Pada Mata Kuliah Metode Penginjilan Maha-siswa STT Simpson Ungaran. Penginjilan merupakan Amanat Agung Tuhan Yesus Kristus (Mat. 28:18-20), sehingga STT Simpson menekankan pada pemenuhan Amanat Agung tersebut. Penelitian ini mengu-raikan tentang capaian pelaksanaan praktik PI dan apa saja yang menjadi faktor penghambat pelaksanaan praktik Metode PI pada mahasiswa peserta mata kuliah Metode PI semester Genap tahun ajaran 2014-2015. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Data dalam pene-litian ini diperoleh melalui FGD, wawancara terbuka, dan laporan praktik mahasiswa. Hasil penelitian yang diperoleh adalah 1) Capaian praktik mahasiswa hanya sampai pada tahap penyampaian Injil, 2) Fak-tor kesulitan melaksanakan praktik PI adalah faktor internal: 55,55%, dan faktor eksternal: 44,44%.